2009
DOI: 10.1007/s10479-009-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

The three-factor model and artificial neural networks: predicting stock price movement in China

Abstract: Since the establishment of the Shanghai Stock Exchange (SHSE) in 1990 and the Shenzhen Stock Exchange (SZSE) in 1991, China's stock markets have expanded rapidly. Although this rapid growth has attracted considerable academic interest, few studies have examined the ability of conventional financial models to predict the share price movements of Chinese stock. This gap in the literature is significant, given the volatility of the Chinese stock markets and the added risk that arises from the Chinese legal and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…After addressing the input-output relationship from the social media data, ANN can be used to formulate such a relationship mathematically. ANN is a non-linear regression model which has been widely used for regression and predictive purposes such as stock market forecasting [26], credit rating [27], and consumer analysis [28]. Its application to social media data however is somehow limited.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…After addressing the input-output relationship from the social media data, ANN can be used to formulate such a relationship mathematically. ANN is a non-linear regression model which has been widely used for regression and predictive purposes such as stock market forecasting [26], credit rating [27], and consumer analysis [28]. Its application to social media data however is somehow limited.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Wei et al () proposed an ANN‐based fuzzy model to predict the stock price trend in the Taiwan Stock Exchange and found that the proposed model has superior prediction power compared with previous fuzzy models, such as those of Yu () and Chen (). Cao et al () compared the predictive ability of ANN models with the dynamic versions of a single‐factor capital asset pricing model (CAPM)‐based model and Fama–French's three‐factor model in predicting stock price movement in China and reported that the ANN model outperformed the CAPM‐based models and proved to be a useful tool for stock price prediction in emerging markets. Hsieh et al () also investigated the forecasting of stock price index's direction using an ANN‐based model and successfully applied it to the DJIA Index, London FTSE‐100 Index, Tokyo Nikkei‐225 Index (Nikkei), and Taiwan Stock Exchange Capitalization Weighted Stock Index (TAIEX).…”
Section: Artificial Neural Network Modelling and Literature Reviewmentioning
confidence: 99%
“…There are 598 price values in each company, thus a company with 0.5% missing data will have 3 missing weekly price values from the year 2000 to 2011. 5 5 Missing data are estimated by the linear interpolation using formulas (1), (2) and (3).…”
Section: Estimated Missing Datamentioning
confidence: 99%
“…The grouped portfolios are shown below in table (2). There are 13 portfolios and each contains over 10 companies.…”
Section: Portfoliosmentioning
confidence: 99%